(untitled) (Revista de Ciências Agroveterinárias, 2025)
The longevity of coffee plantations reflects the health of the plant material, the management of seedling production in nurseries, and the use of appropriate techniques in the establishment of coffee crops. This study focused on evaluating the effect of coffee seedlings produced in bags and tubes on the vegetative parameters and productivity of the coffee crop, cultivar IPR 100. The experiment was conducted at Fazenda Bordin, located in Monte Carmelo, Minas Gerais, using a rainfed system. A randomized block design was used, with eight blocks and three treatments, namely: T1 - Seedlings planted with polyethylene bags containing 84 holes; T2 - Seedlings planted with the removal of polyethylene bags containing 84 holes; and T3 - Seedlings produced in tubes. Assessments of plant height, stem diameter, and crown diameter were conducted monthly from May 2018 to April 2020. In June 2020, the first harvest was carried out, evaluating productivity (60 kg bags per hectare), grain classification in terms of size and shape, and percentage of ripeness. The results suggest that the packaging used in the production of IPR100 seedlings was not a decisive factor in the development, production, grain quality, and maturation for the plants’ first production cycle. It is concluded that in the production of healthy seedlings in a more sustainable manner, the use of tubes should be considered. Compared to plastic bags, the tube offers important advantages such as reusability, preventing soil contamination with non-degradable plastics; reducing the risk of biological contamination with pathogens; and facilitating nursery operations, shipping, and crop planting without compromising the productivity of the first harvest of the IPR100 cultivar.